The Effect of Working Capital Management, Leverage Policy, and Liquidity on Financial Performance in Construction Companies in Indonesia - Judijanto, Loso; Ambarwati, Retnoning (Westscience Press, 2024)
This study examines the impact of capital management, leverage policy, and liquidity on the financial performance of construction companies in Indonesia. A quantitative research approach was utilized, involving 130 construction firms. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to assess the relationships between variables. Results indicate that effective capital management and prudent leverage policy significantly enhance financial performance, while liquidity demonstrates the strongest positive effect. This highlights the critical role of an integrated financial strategy, particularly in managing liquidity, to navigate cash flow uncertainties and improve profitability. The findings provide practical insights for construction firms in optimizing financial strategies to achieve resilience and sustainable growth.